Depression and Alcohol Use in a National Sample of Hispanic Adolescents. (16th April 2018) - Merianos, Ashley L.; Swoboda, Christopher M.; Oluwoye, Oladunni A.; Gilreath, Tamika D.; Unger, Jennifer B.
ABSTRACT: Background : Underage alcohol use and depression remain public health concerns for Hispanic adolescents nationwide. Objectives : The study purpose was to identify the profiles of depression among Hispanic adolescents who reported experiencing depressive symptoms in their lifetime and classify them into groups based on their symptoms. Based on classifications, we examined the relationship between past year alcohol use and severity of depressive symptoms while controlling for sex and age. Methods : A secondary analysis of the 2013 NSDUH was conducted among Hispanic adolescents from 12 to 17 years of age ( n = 585) who reported experiencing depressive symptoms. Latent class analysis was used to identify latent classes of depressive symptoms among Hispanic adolescents. A zero-inflated negative-binomial regression model was used to examine the relationship between alcohol use and depressive symptoms. Results : "High depressive" and "moderate depressive" classes were formed. The items that highly differentiated among the groups were felt worthless nearly every day, others noticed they were restless or lethargic, and had changes in appetite or weight. There was a significant difference ( p = 0.03) between the classes based on alcohol use; those in the moderate depressive class were 1.71 times more likely to be identified as not reporting past alcohol use. Results indicated the high depressive class was estimated to have 1.62 more days of past year alcohol use than those in the moderate depressive class for adolescents who used alcohol ( p < 0.001). Conclusions/Importance : Study findings can be used to address these significant public health issues impacting Hispanic adolescents. Recommendations are included.